Full range resistive thermometers. (December 2015) - Olivieri, E.; Rotter, M.; De Combarieu, M.; Forget, P.; Marrache-Kikuchi, C.; Pari, P.
Highlights: We present a method to obtain resistive thermometers operating in the 10 mK to 300 K range. The thermometer has an electrical resistance adapted to commercial AC resistance bridges. The thermometer has an almost constant, negative, dimensionless sensitivity in the whole 10 mK–300 K temperature range. A calibration technique is detailed described to establish the resistance versus temperature curve. We present time-response and thermal conductance of the a typical full range thermometer. Abstract: Resistive thermometers are widely used in low temperature physics, thanks to portability, simplicity of operation and reduced size. The possibility to precisely follow the temperature from room temperature down to the mK region is of major interest for numerous applications, although no single thermometer can nowadays cover this entire temperature range. In this article we report on a method to realize a full range thermometer, capable to measure, by itself, temperatures in the whole above-cited temperature range, with constant sensitivity and sufficient precision for the typical cryogenic applications. We present here the first results for three different full range thermometer prototypes. A detailed description of the set-up used for measurements and characterization is also reported.